Cambodian Dollarization : Its Policy Implications for LDCs' Financial Development. - Okuda, Hidenobu; Chea, Serey (Milton : Taylor & Francis Group, 2023)
This book is the first study to provide a comprehensive picture of the reality and structure of dollarization in Cambodia, which has been achieving rapid economic and financial development since the 2000s. It uses data collected through nationwide surveys conducted by the National Bank of Cambodia and JICA Ogata Sadako Research Institute.
7.3.3 International Trade, Invoicing, and Dollarization -- 7.4 Financial Dollarization in the Highly Integrated International Market -- 7.4.1 Dollarization of Assets -- 7.4.2 Dollarization and Overseas Assets -- 7.4.3 Dollarization of Liability -- 7.5 Conclusion: Coping With Partial Dollarization -- References -- 8 Strategies for Promotion of Khmer Riel -- 8.1 Introduction -- 8.2 De-Dollarization Policies Until Recently -- 8.2.1 Enhance Confidence in the Riel -- 8.2.2 Promote Price Quotations and Payments of Goods and Services in Riel -- 8.2.3 Promote the Opening of Bank Accounts in Riel -- 8.2.4 Improve the Payment System and Financial Instruments in Riel -- 8.3 De-Dollarization Policy and Financial Market Development -- 8.3.1 Improve Foreign Exchange Markets -- 8.3.2 Further Developing Interbank and Money Markets -- 8.3.3 Further Develop Securities Markets -- 8.3.4 Broaden the Clearing House's Policy On Lowering the Riel Transaction Fee to Market Fund Transfer -- 8.4 New Elements for the Promotion of Khmer Riel -- 8.4.1 Promote Financial Intermediation in Riel On a Gradual Basis -- 8.4.2 Fiscal Support for the Riel -- 8.4.3 Promote Public Awareness and Participation -- 8.4.4 Enhance Cooperation for the Implementation of Effective Measures -- 8.5 Effectiveness of Promoting the Policy and Its Limitations -- 8.5.1 Stronger Yet Still Limited Confidence -- 8.5.2 Difficulty in Changing People's Mindset -- 8.5.3 Network Externality -- 8.5.4 Lack of Demand-Side Policies -- 8.5.5 Limited Domestic Production -- 8.5.6 Limited Coordination Between Implementing Agencies -- 8.6 Conclusion -- Notes -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books